Additive Manufacturing: A Key to Advancing Injection Molding Efficiency - Mladomir Milutinović; Dejan Movrin; Miloš Pjević; Mihajlo Popović (Tehnički Glasnik)
The increasing demand for custom-made products, small-batch production, and improved process efficiency is driving manufacturers to adopt advanced strategies that minimize costs and production time. Additive manufacturing (AM) technologies address these challenges by enabling rapid prototyping, design flexibility, and advanced tooling capabilities. Initially constrained to polymeric prototypes, AM now supports a diverse material range, including metals and temperature-resistant polymers. Injection molding is a widely used manufacturing process for producing plastic parts with high precision and repeatability. However, traditional injection molding faces challenges such as high tooling costs, long lead times, and design limitations. This paper investigates solutions to these challenges through the application of additive manufacturing and rapid tooling technologies, emphasizing their potential to transform efficiency in injection molding.